TESTS TO DETERMINATE THE FITNESS LEVEL IN RHYTHMIC GYMNASTICS - Maria Gateva (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2015)
The need of implementing new tests for determining the fitness level of rhythmic gymnasts is vast. 12 high level rhythmic gymnasts were tested in preparatory period with 5 tests - two laboratory tests on a treadmill (VO2max and 2 min submaximal test) and three field tests (2 min shuttle run test, modified gymnastics routine and rhythmic gymnastics routine) to determine the fitness level of the gymnasts. VO2max was completed in order to calculate the individual 90-95% for the 2 min submaximal test. All the other tests were set to respond to the same load as the competitive program in rhythmic gymnastics - the routine. The differences between the tests, based on the HR and blood lactate give us reason to believe that the test loads should be selected more precisely. The routine still displayed higher demands upon the gymnasts' body systems compared to the other three applied tests. The shuttle run tests gave the closest values of HR compared to the routine load. Submaximal laboratory test have to be increased by 1-2% in order to cause the same reaction to the gymnasts' body as the routine.